MANAGERS' VIEWS ON TEACHING WORK CONDITIONS IN THE INTEGRAL EDUCATION PROGRAM - Rinaldi, Renata Portela [UNESP]; Ulloffo, Renan Moreira [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2023)
This qualitative research aims to analyze the conditions of teaching work in the Integral Education Program, from the perspective of the school management team. Data collection took place through a questionnaire and semi-structured interview. From the descriptive-interpretative analysis, we identified positive aspects and weaknesses in the program, such as exclusive dedication made possible by the RDPI and the salary increase through the GDPI. About weaknesses: a possible technicist character, pressure for good performance through evaluations, absence of substitute professionals, increase in the number of classes, decrease in the teaching staff, work overload and lack of continuing education actions. Therefore, although the PEI has aspects that can contribute to good working conditions and, consequently, the promotion of good quality education, the program is the result of the nuances of neoliberal reforms that worsen and make working conditions precarious over the years.
Keywords: Integral Education Program; School management; Teaching work